Show and explain how replacing one equation by the
sum of that equation and a multiple of the other produces
a system with the same solutions as the one shown.
8x + 7y = 39
4x – 14y = -68

Respuesta :

Answer:

x = 1/2 and y = 5

Step-by-step explanation:

First, let's multiply the first equation by two on the both sides:

[tex]8x + 7y = 39 \times 2[/tex]

⇒ [tex]16x + 14y = 78[/tex]

Now, the system is:

[tex]16x + 14y = 78\\\\4x -14y = -68[/tex]

After adding this up in the column:

[tex](16x + 4x) + (14y - 14y) = 78 - 68\\\\20x = 10\\\\ x = 10/20 = 1/2[/tex]

y can be calculated by replacin the x:

[tex]8x + 7y = 39\\\\ 8* 1/2 + 7y = 39\\\\4 + 7y = 39\\\\7y = 39 - 4\\\\7y = 35\\\\ y = \frac{35}{7} = 5[/tex]

x = 1/2 and y = 5

The solution to the system of equation are as follows:

x =  1 /2 and y  = 5

8x + 7y = 39

4x – 14y = -68

multiply equation(1) by 2

Therefore,

  • 16x + 14y = 78

Therefore, the combine equation is as follows:

Simultaneous equation:

16x + 14y = 78

4x - 14y = -68

let's add the equations

(16x + 4x) + (14y + (-14y)) = 78 - 68

20x = 10

x = 10 / 20

x = 1 / 2

Replace the value of x in equation(ii)

4(1 /2) - 14y = -68

2 - 14y = -68

-14y = -68 - 2

-14y = -70

y = - 70 / - 14

y = 10 / 2

y = 5

learn more on system of equation: https://brainly.com/question/1415383?referrer=searchResults